EBV-specific T-cell immunity in pediatric solid organ graft recipients with posttransplantation lymphoproliferative disease - Wilsdorf, Nadine; Eiz-Vesper, Britta; Henke-Gendo, Cornelia; Diestelhorst, Jana; Oschlies, Ilske; Hussein, Kais; Pape, Lars; Baumann, Ulrich; Tönshoff, Burkhard; Pohl, Martin; Höcker, Britta; Wingen, Anne-Margret; et al. (Transplantation, 2013)
Background: Posttransplantation lymphoproliferative disease (PTLD) is an often Epstein-Barr virus (EBV)-associated mainly malignant complication after transplantation. We present data on EBV-specific T cells in children treated with rituximab with or without chemotherapy on the pediatric PTLD Pilot 2005 protocol. - Methods. Peripheral blood mononuclear cells were isolated from 16 pediatric patients with PTLD, 4 transplanted children with EBV reactivation, and 18 healthy controls. EBV-specific T cells were quantified by flow cytometric detection of intracellular interferon-γ after stimulation with autologous EBV-transformed lymphoblastoid cell lines and correlated with EBV load in peripheral blood. - Results: At diagnosis, PTLD patients had similar numbers of EBV-specific CD4+ and CD8+ T cells as healthy EBV-positive controls. EBV-specific T cells tended to be lower in early PTLD compared with late PTLD. During treatment with rituximab, CD4+ and/or CD8+ EBV-specific T cells increased in most patients, possibly reflecting restored immunocompetence due to a reduction of immunosuppression as well as antigenic stimulation by cross-presentation of EBV antigen from destroyed B cells. However, this increase did not predict response to rituximab or chemotherapy. EBV load and circulating B cells became undetectable in most patients during rituximab therapy. B-cell recovery after treatment was accompanied by redetection of EBV in peripheral blood, which was controlled by T-cell responses in 11 of 11 evaluable cases. - Conclusions: In pediatric PTLD patients, pretreatment EBV-specific T-cell numbers are in the range of healthy controls. These cells increased on reduction of immunosuppression and treatment with rituximab. Recurrence of EBV viremia during complete remission is matched by strong T-cell responses.